Attitude of health care workers to the involvement of alternative healthcare providers in the home management of childhood malaria (2005)
The attitudes of 193 healthcare workers (Nurses (35.7%), auxiliary nurses' (35.7%), followed by community health officers (26.4%) in 55 primary and secondary healthcare facilities to home management of malaria were evaluated in four local government areas in Southwestern Nigeria. Results showed that mothers and patent medicine sellers were perceived as offering useful services in home management of malaria by giving first aid and selling antimalaria drugs, respectively. Although 79% of respondents expressed the opinion that mothers are the most appropriate to give first line management to children suffering from malaria, 56% were also of the view that such children should receive definitive treatment in a formal health care facility. Furthermore, 45% of the respondents felt that only formal healthcare workers should treat children who have malaria irrespective of the location of the treatment because mothers, patent medicine sellers, and traditional healers have not been formally trained. Healthcare workers were willing to train mothers and patent medicine sellers on effective management of childhood malaria, but were not favorably disposed toward collaboration with traditional healers in the home management of malaria. There is an urgent need for formal healthcare workers to seek better understanding of traditional healers' practices as well as their cooperation for improved home management of childhood malaria among indigenous groups.